Enthesitis of Plantar Fascia Affects Gait in Patients With Ankylosing Spondylitis - Yentur, Songul Baglan; Bilek, Furkan; Deniz, Gulnihal; Akgol, Gurkan; Koca, Sueleyman Serdar (Amer Podiatric Med Assoc, 2024)
Background: Many factors, such as decreased spinal mobility, pain, and dysfunction can affect gait parameters in patients with ankylosing spondylitis. The purpose of this study was to investigate the effects of plantar fascia enthesitis and disease-specific measurements on gait parameters in patients with ankylosing spondylitis. Methods: The Win-Track platform was used to evaluate spatiotemporal parameters in patients with ankylosing spondylitis and in healthy controls. The Bath Ankylosing Spondylitis Metrology Index (BASMI), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and Bath Ankylosing Spondylitis Function Index (BASFI) were used for disease-related parameters in patients with ankylosing spondylitis, respectively. Tendon thickness in the plantar fascia was measured using ultrasound to evaluate enthesitis. Results: Thirty-one patients with ankylosing spondylitis and 31 healthy participants were included in the study. Cadence and step-cycle duration had a significant relationship with enthesitis for all regions and disease-related measurements. In addition, step length had a significant relationship with enthesitis for the midfoot and metatarsal bones, BASMI, and BASDAI; the left step length had a significant relationship with enthesitis in the calcaneus. The double-support phase had a significant relationship with enthesitis and BASMI. In the regression analysis, a significant relationship was found between BASDAI and step cycle time. A significant correlation was observed between all ultrasonographic parameters and cadence and stride cycle time values. Conclusions: Impaired gait parameters were found in ankylosing spondylitis patients, and we concluded that plantar fascia enthesitis, function, disease activity, and spinal mobility affect gait parameters for these patients. Therefore, therapy for enthesitis, and adding foot rehabilitation to the routine program should be considered for patients with ankylosing spondylitis.
Keywords: Bath; Walking; Index